Al-Khalil bin Ahmad al-Farahidi in Formulating the Principles of Nahwu Science: Traces of Thought and Influence on the Transformation of the Arabic Language - Mahdi, Muhammad; Viyan Sutobri; Rosalia Indah (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Al-Khalil bin Ahmad al-Farahidi is a key figure in the development of nahwu and sharf. This study examines his contributions to Arabic grammar and its impact on language transformation. Using a descriptive-analytical approach, this library research reveals that Al-Khalil played a major role in codifying the Arabic vowel system, classifying words into isim, fi’il, and harf, and introducing key grammatical terms. His influence is evident in Al-Kitâb, written by his student Sibawaih. Additionally, he contributed to phonology, morphology, ‘arudh, and compiled the first Arabic dictionary, Kitāb al-‘Ain. His legacy continues to shape Arabic linguistics academically and in modern education. This study reaffirms Al-Khalil’s fundamental role in Arabic grammar.